Interrelated Oncogenic Viruses and Breast Cancer - Afzal, Samia; Fiaz, Khadija; Noor, Afifa; Sindhu, Amira Saleem; Hanif, Asma; Bibi, Ayesha; Asad, Muhammad; Nawaz, Saba; Zafar, Saba; Ayub, Sidra; Hasnain, Syeda Bariyyah; Shahid, Muhammad (Frontiers in Molecular Biosciences, 2022)
Breast Cancer is a multifactorial disease and recent evidence that viruses have a greater role in its aetiology and pathophysiology than previously hypothesized, has garnered a lot of attention in the past couple of years. After the role of Mouse Mammary Tumour Virus (MMTV) in the oncogenesis of breast cancer has been proved in mice, search for similar viruses found quite a plausible relation of Human Papilloma Virus (HPV), Epstein - Barr virus (EBV), and Bovine Leukaemia Virus (BLV) with breast cancer. However, despite practical efforts to provide some clarity in this issue, the evidence that viruses cause breast cancer still remains inconclusive. Therefore, this article aims to clarify some ambiguity and elucidate the correlation of breast cancer and those particular viruses which are found to bring about the development of tumorigenesis by a previous infection or by their own oncogenic ability to manipulate the molecular mechanisms and bypass the immune system of the human body. Although many studies have reported, both, the individual and co-existing presence of HPV, EBV, MMTV, and BLV in patient sample tissues, particularly in Western women, and proposed oncogenic mechanisms, majority of the collective survey of literature fails to provide a delineated and strong conclusive evidence that viruses do, in fact, cause breast cancer. Measures to prevent these viral infections may curb breast cancer cases, especially in the West. More studies are needed to provide a definite conclusion.